The residual stress of the cold rolled bearing race. (2017) - Lan, Jian; Feng, Shaogui; Hua, Lin
Abstract: Cold ring rolling is new process for the manufacturing of high precision bearing race, which only need grinding instead of large amount of cutting, because this new process can provide good roundness of semi-finished bearing race. But the cold ring rolling process also induces uneven residual stress across the thickness of bearing race, which may cause the unpredicted deflection of the bearing race during and after heat treatment and service period. It is very important to predict and control the residual stress of the cold rolled bearing race. The bearing race is made of GCr15 alloy steel. The surface residual stresses of the rolled bearing race were observed by X-ray Diffraction machine, X-350A. To obtain the residual stresses across the thickness of the bearing race, the material was etched off and then measured. Those residual stresses are used to construct the real residual stress before material etched. The spheroidizing annealed GCr15 alloy steel samples were loaded and reverse loaded to obtain the nonlinear isotropic/kinematic hardening model of the bearing material. The hardening model was used to simulate the bearing race rolling and predict the residual stress, and provides a way to predict the residual stress of cold rolled ring.